ANALYTIC STUDY OF THERMOHALINE CONVECTIVE STABILITY IN A COUPLE-STRESS FLUID - Reeta Devi,; Choudhary, Shalu; Poonam Sharma,; Sunil,; Manoj Kumar Sharma,; Mayank Singh,; Prayas Chaudhary,; Muskan Rawat, (Malaysian Journal of Science, 2024)
This work investigates nonlinear analysis for thermohaline convective stability in a steady, viscous, incompressible couple-stress fluid by performing a generalized energy method. It is observed that the linear and nonlinear threshold that reflects the physics of the onset of convection is the same. The couple stress and solute gradient are seen to have a stabilizing impact on the system.